Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1161/circulationaha.110.971168
|View full text |Cite|
|
Sign up to set email alerts
|

Part 13: First Aid

Abstract: The International First Aid Science Advisory Board identified 38 questions in first aid practice that had not been subjected to an evidence review process or that needed to be updated since the 2005 process. Two or more members of the International First Aid Science Advisory Board volunteered to independently review the scientific literature and complete an evidence-based review worksheet summarizing the literature (see Part 2 of this supplement for additional information). After the evidence was presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 284 publications
0
43
0
2
Order By: Relevance
“…It also stated that if an individual with a suspected cervical spine injury had to be turned onto his or her side, the high arm in endangered spine (HAINES) position seemed to be safer. 10 An extensive literature search and use of GRADE methodology resulted in some studies from the 2010 review being excluded from the 2015 review and other newly identified studies being included. The revised 2015 recommendations reflect this rigorous evidence evaluation process.…”
Section: Introductionmentioning
confidence: 99%
“…It also stated that if an individual with a suspected cervical spine injury had to be turned onto his or her side, the high arm in endangered spine (HAINES) position seemed to be safer. 10 An extensive literature search and use of GRADE methodology resulted in some studies from the 2010 review being excluded from the 2015 review and other newly identified studies being included. The revised 2015 recommendations reflect this rigorous evidence evaluation process.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2010 review of educational topics, no evidence was found to support or recommend any method of evaluating or monitoring a first aid trainee's educational progress or the specific frequency of retraining to retain skills and knowledge. 133 The task force decided to investigate the basic question, is there documented evidence of benefit in terms of patient outcomes as a result of first aid training?…”
Section: Educationmentioning
confidence: 99%
“…The aim of this procedure is to improve blood circulation by facilitating venous return from the lower limbs [1][2][3][4][5][6][7][8][9][10]. However, several studies have cast doubts on the efficacy and duration of the effects of PLR [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have cast doubts on the efficacy and duration of the effects of PLR [2][3][4]. Possibly due to this controversy, in the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care of 2010 [8], PLR was neither recommended nor prohibited for the treatment of hypovolemic shock.…”
Section: Introductionmentioning
confidence: 99%